Quantitative Evaluation of Economic and Social Development of Lithuanian Regions - Ginevičius, R.; Podvezko, V.; Mikelis, D. (Ekonomika, 2004)
Many European countries are faced with the problem of regional disparities when the level of social and economic development of particular regions is dramatically different. This causes social conflicts. In developing the effective regional policy one of the most important conditions is the identification of the actual level of development of a region. This problem may be solved if economic, social. political, legislative, ecological and other factors influencing regional development are taken into consideration.For this purpose, a comprehensive system of criteria should be developed, with their subsequent integration into a unified criterion.In the present paper, a set of criteria for evaluating regional development based on practical expertise and theoretical analysis is suggested. They embrace economic, innovational. social and other aspects of development.The criteria reflecting economic and social development of a region are multidimensional and of opposite directivity, therefore. they are normalized in accordance with the aggregation technique used.